Prevalência de incontinência urinária e fecal e fatores associados no escopo da síndrome da fragilidade em idosos comunitários: estudo da rede fibra - Márcio Moreira Silva Brito (2015)
The frailty is characterized by loss of adaptive capacity and decline in functionality resulting higher prevalence of geriatric syndromes such as incontinences. However, few studies describing the relationship between incontinences and frailty. The objective of this study was to investigate the strength of association and their degree of magnitude between the types of incontinences, frailty, medical conditions, sociodemographic, functional performance measures and overall life satisfaction in older from four cities in different regions of the country under the Network database Fragility Studies in Elderly Brazilians (FIBER Network) in UFMG pole. The sample consisted of 1756 elderly (65 and over), able to walk and without cognitive deficits. The fragility was evaluated based on frailty phenotype. The incontinence were operationalized by the questions "Mr (s) have urinary incontinence (involuntary loss of urine)" or "Mr (s) have fecal incontinence (involuntary loss of feces)"? The functional performance was obtained by the scale of Lawton (instrumental activities of daily living) and the presence of depressive symptoms (Geriatric Depression Scale - GDS). The number of falls, medications and overall satisfaction with life and the referenced fields (SGV) were collected by structured questionnaire. Descriptive statistics were used to explore the selected variables; to verify the association between socio-clinical and demographic variables and the prevalence of weakness, urinary incontinence, fecal and double between cities interaction tests were used; to determine the differences and associations between groups of incontinence and socio-clinical and demographic variables we used the ANOVA Kruskal-Wallis test and Mann-Whitney post-test, in case of categorical variables, and chi-square in case of continuous variables. Later factorial ANOVA was performed to check interactions between the profile of frailty and incontinence groups in determining the independent variables. In Santa Cruz the prevalence of urinary incontinence (24.6%) and double (4.9%) were higher; and Belo Horizonte, higher prevalence of fecal incontinence (3.5%). Incontinence groups differed between cities (p = 0.002). In the overall sample 10.1% of the elderly were classified as frail, 47.1% pre-frail and 42.8% non-frail (p <0.0001) and the frailty profile also differed between cities (p <0, 0001). Socio- Demographic and clinical variables associated with incontinence groups were gender (p <0.0001), age (p = 0.003) and level of frailty (p <0.0001). The prevalence of frailty elderly was higher in groups of elderly people with urinary and fecal incontinence. The prevalence of urinary and fecal incontinence was higher among elderly 80+ compared to the group of 65-79 years (p = 0.047 and p = 0.003, respectively). Urinary and fecal incontinence was more prevalent in women (p <0.0001 and p = 0.006, respectively). There was a combined effect of frailty and incontinences in determining the number of falls (p = 0.006), number of medications (p = 0.023), IADL score and score for GDS (p <0.0001). The incontinence and frailty are closely linked and to identify factors associated with the frailty syndrome and incontinences may contribute to the development of therapeutic actions and public policies for preventing negative outcomes to the health of the elderly.